(Z, E)‐α‐Farnesene – sex pheromone component of female click beetle Selatosomus aeripennis destructor with intra‐ and inter‐sexual communication function. Issue 4 (25th January 2022) - Gries, Regine; van Herk, Wim; Alamsetti, Santosh K.; Catton, Haley; Meers, Scott; Otani, Jennifer; Gries, Gerhard
Abstract: Sex pheromones are known for only a few major click beetle (Coleoptera: Elateridae) pests in North America. These pheromones could be used to monitor, as well as control, adult beetles. Our objective was to identify the sex pheromone of female Selatosomus aeripennis destructor (Brown), a predominant elaterid pest species in farmland in the Canadian Prairie provinces. Headspace volatiles from a group of S . a . destructor females were collected and analyzed by coupled gas chromatography‐electroantennographic detection (GC‐EAD) and gas chromatography‐mass spectrometry (GC‐MS). The GC‐EAD recordings revealed two candidate pheromone components that elicited weak (CPC‐1) or strong (CPC‐2) responses from adult male S. a. destructor antennae. The mass spectra of CPC‐1 and CPC‐2 indicated, and authentic standards confirmed, that they were the isomers ( E )‐β‐farnesene and ( Z, E )‐α‐farnesene, respectively. In three field experiments at various sites in Alberta, Canada, traps baited with synthetic ( Z, E )‐α‐farnesene captured 7.1×, 6.8×, and 2.6× more males than unbaited control traps. In follow‐up experiments, traps baited with ( Z, E )‐α‐farnesene captured significantly more males, but significantly fewer females, than unbaited control traps, indicating sex pheromone autodetection by females. ( E )‐β‐Farnesene on its own was not attractive as a trap lure, and when added to ( Z, E )‐α‐farnesene at a 20:1 ratio, it reduced the lure's attractiveness. Our data support the conclusion that ( Z, E )‐α‐farnesene is the major sex pheromone component of S. a. destructor females, with both an intra‐ and inter‐sexual communication function. Abstract : The click beetle Selatosomus aeripennis destructor (Coleoptera: Elateridae) is an important pest in Canada. We aimed to identify its sex pheromone, which could be used for monitoring and control. Analyses of female headspace volatiles revealed two isomers as pheromone candidates: ( Z, E )‐α‐farnesene and ( E )‐β‐farnesene. In field experiments, traps baited with synthetic ( Z, E )‐α‐farnesene captured more males, but fewer females, than unbaited controls. Adding ( E )‐β‐farnesene (20:1 ratio) decreased attractiveness. Thus, ( Z, E )‐α‐farnesene is the major sex pheromone component, with intra‐ and inter‐sexual communication functions.